Perceptions of Gender Disparities in Vietnam’s Labor Market - World Bank (World Bank, Washington, DC, 2020)
In the context of Vietnam’s impressive economic growth over the last two decades, several studies have documented gender disparities, but few have studied the underlying constraints that drive the disparities. The Vietnamese government is working to increase its support to job seekers. To help fill the knowledge gaps, this study uses three qualitative methods to understand stakeholders’ views on the mechanisms underlying gender disparities in the Vietnamese labor market and related policy: (1) individual biographical interviews; (2) focus group discussions; and (3) expert interviews. This study gives particular emphasis to the context in which the gender dynamic is played out in the sphere of the labor market. It approaches gender not as naturally determined but as socially constructed, with cultural, political, religious, and ethnical concepts all influencing its meaning. The study’s qualitative findings confirm that a range of gender disparities exist in Vietnam’s labor market. Section one gives introduction. Section two provides information on the institutional and legal environment in Vietnam and summarizes existing findings on gender disparities in the country’s labor market. Section three describes the qualitative methodologies that were used in the study, namely individual biographical interviews, focus group discussions, and key informant interviews. Section four discusses the empirical findings, section five details summary of research results for the provinces of Dien Bien and Quang Nam, and section six presents conclusions and policy recommendations.